2022
DOI: 10.3389/fcimb.2022.980817
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from Trypanosoma cruzi-dendritic cell interaction show modulatory properties and confer resistance to lethal infection as a cell-free based therapy strategy

Abstract: Extracellular vesicles (EVs) include a heterogeneous group of particles. Microvesicles, apoptotic bodies and exosomes are the most characterized vesicles. They can be distinguished by their size, morphology, origin and molecular composition. To date, increasing studies demonstrate that EVs mediate intercellular communication. EVs reach considerable interest in the scientific community due to their role in diverse processes including antigen-presentation, stimulation of anti-tumoral immune responses, tolerogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Recently, EVs have gained attention in translational applications, from the discovery of biomarkers for diseases, to their roles in drug delivery systems. For example, the work by Gutierrez et al (2022) [ 28 ] showed that EVs derived from the interaction of T. cruzi trypomastigotes with dendritic cells conferred protection to animals challenged with lethal infection by T. cruzi . Furthermore, the potential of EVs present in the serum of S. aureus osteomyelitis patients to facilitate the diagnosis has already been discussed [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, EVs have gained attention in translational applications, from the discovery of biomarkers for diseases, to their roles in drug delivery systems. For example, the work by Gutierrez et al (2022) [ 28 ] showed that EVs derived from the interaction of T. cruzi trypomastigotes with dendritic cells conferred protection to animals challenged with lethal infection by T. cruzi . Furthermore, the potential of EVs present in the serum of S. aureus osteomyelitis patients to facilitate the diagnosis has already been discussed [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…While these proteins have not yet shown promise as vaccine candidates, the mucin‐like‐associated surface protein (MASP) family, a virulence factor involved in host‐cell invasion, has shown the ability to induce a humoral and cellular response and reduce parasite load when used in immunisation of mice [50]. Recently, a single dose of T. cruzi ‐pulsed dendritic cell (DC) EVs has been shown to induce a protective cellular immune response, reduce parasite load and increase survival of mice after infection with a lethal strain [51]. However, this strategy using DCs is limited by its high cost and the challenges of delivering the antigen effectively.…”
Section: Can Extracellular Vesicles Aid Vaccine Development?mentioning
confidence: 99%
“…For example, it was found that sera from patients with CD was immunoreactive to proteins present in EVs, placing these particles as a possible biomarker of CD [138]. Regarding vaccines, Gutierrez et al [143] showed that EVs from the interaction between blood trypomastigotes and bone marrow-derived DCs confer partial protection in animals challenged with lethal T. cruzi infection. These results, together with reports on other pathogens such as Toxoplasma gondii [144,145], Eimeria spp.…”
Section: Preference or Restriction To A Certain Host Tissue? Factors ...mentioning
confidence: 99%